The Relationship between Economic Growth and the Generation of Urban Solid Waste - Lebrego Cardoso, Emile; Pereira Santos, Vanusa Carla; Raiol de Campos, Raul Ivan; da Cunha, Jéssica Almeida (Revista Gestão & Sustentabilidade, 2025)
This study examined the relationship between economic growth and solid waste generation, aiming to analyze the correlation between economic growth represented by Brazil's Gross Domestic Product (GDP) from 2012 to 2019 and the generation of Urban Solid Waste during the same period. This analysis was based on the theory of Ecological Economics, specifically the second law of thermodynamics, the law of entropy, which states that the economic system extracts resources and low-entropy matter from the environment and returns high-entropy energy and matter, representing environmental degradation and disorder. The main objective of this study was to verify through descriptive statistics if there is a direct correlation between economic growth (GDP) and the generation of Urban Solid Waste (USW) measured in thousand tons per day, representing high entropy. There is a direct relationship between GDP growth and the generation of USW, which raises the research question: how is it possible to control and manage the generation of USW in the face of GDP growth? The methodology involved bibliographic, qualitative, and quantitative research, utilizing statistical data such as Pearson's correlation coefficient. The results indicate a significant correlation between GDP growth and USW generation, demonstrating a consistent increase in USW when there is a peak in GDP growth. This suggests that society tends to consume more disposable products in daily life, contributing to waste generation. The conclusion drawn was that GDP growth has become unsustainable as it fails to preserve natural resources and mitigate waste disposal and environmental damage caused by economic activities.